Tuning ZnO with Er: Structural effects, spin-resolved electronic states, and optical response - Orek, Cahit (Springer, 2026)
Context This study examines how spin multiplicity governs the structure, electronic states, magnetism, and optics of Er-doped ZnO nanostructures. Substitutional Er3+ at Zn sites slightly elongates Er-O bonds while preserving the Zn-O framework, consistent with prior experiments. Energetically, the triplet and quintet states are nearly degenerate and substantially more stable than the singlet, identifying both magnetic states as relevant. Spin polarization reorganizes frontier levels and introduces Er-centered localized states; in the magnetic states, the Kohn-Sham HOMO-LUMO separation is similar to 1.8 eV. The Er-4f moment couples mainly through O-2p, with assistance from Zn(s + p), yielding weakened net ferromagnetism in the triplet and stronger parallel alignment in the quintet. Simulated spectra show a blue-shifted UV edge near similar to 3.9 eV relative to pristine ZnO and weak visible shoulders at similar to 2.1 and similar to 2.8 eV, consistent with partially allowed Er3+ intra-4f transitions. Methods Finite ZnO clusters were treated with spin-polarized hybrid DFT using the range-separated CAM-B3LYP functional. Geometry optimizations were performed without symmetry constraints, followed by electronic-structure analyses for singlet (S = 0), triplet (S = 1), and quintet (S = 2) states. Optical properties were obtained from time-dependent DFT on the optimized spin states. Standard ultrafine integration grids and tight SCF thresholds were used to ensure numerical stability; wavefunction stability checks were applied to open-shell solutions. Calculations were carried out with the Gaussian suite, and postprocessing/visualization employed common electronic-structure analysis tools (molecular orbitals, PDOS, and spin-density mapping).
Keywords: Er-doped ZnO clusters; Spin-resolved DFT; Magnetic ordering; UV-VIS absorption; Burstein-Moss effect; Rare earth doping